Peningkatan Pengetahuan Perilaku Hidup Bersih dan Sehat (PHBS) pada Ibu Rumah Tangga Di Wilayah Kota Tangerang - Oktariani, Liana; Aulia, Isna Dewi; Sari, Ria Setia (Ridwan Institute, 2021)
Clean and healthy living behavior (PHBS) is a step that must be taken to achieve an optimal health degree for everyone. Healthy conditions do not automatically occur, but efforts must always be made from being unhealthy to healthy living and creating a healthy environment. This effort must start from instilling a healthy lifestyle in society that must be started and worked on by oneself. This effort is to realize the highest public health status as an investment for the development of productive human resources. For this reason, the provision of counseling related to clean and healthy living behaviors is expected to be an effort to make people aware of the importance of making efforts to make healthy and clean living Behaviors in their daily life as well as providing knowledge on how to make it happen so that people who care about health are created. The purpose of this activity is to increase housewives' knowledge about PHBS in the household realm. The extension method uses a virtual power point presentation using the google meet application. The level of knowledge of housewives about PHBS before being given PHBS counseling with the percentage of moderate knowledge criteria was 13 people (65%) and the criteria for lack of knowledge were 7 people (35%). While the percentage after being given counseling, the criteria for good knowledge were 17 people (85%) and the moderate criteria were 3 people (15%). This shows that there is an increase in the knowledge of the audience who are housewives between before and after being given PHBS counseling.